2018
DOI: 10.1016/j.aller.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II deficiency: Report of a novel mutation and special review

Abstract: The MHC II deficiency is a rare autosomal recessive primary immunodeficiency syndrome with increased susceptibility to respiratory and gastrointestinal infections, failure to thrive and early mortality. This syndrome is caused by mutations in transcription regulators of the MHC II gene and results in development of blind lymphocytes due to the lack of indicatory MHC II molecules. Despite homogeneity of clinical manifestations of patients with MHC II deficiency, the genetic defects underlying this disease are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
0
22
1
Order By: Relevance
“…In another study, Farrokhi and colleagues reported a 5-year-old Iranian boy with homozygous mutation in RFXANK gene on 19p12 as a substitution of G with A in TGG codon for W188 that resulted in a premature stop codon creation in exon 3 and caused recurrent fever, diarrhoea, failure to thrive, upper respiratory tract infection, and oral lesions since four months of age. 11 The reported mutation in this study is different from our presented case but was similarly in the RFXANK gene. As this mutation is considered serious and lethal and requires nonconservative treatments like HSCT.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In another study, Farrokhi and colleagues reported a 5-year-old Iranian boy with homozygous mutation in RFXANK gene on 19p12 as a substitution of G with A in TGG codon for W188 that resulted in a premature stop codon creation in exon 3 and caused recurrent fever, diarrhoea, failure to thrive, upper respiratory tract infection, and oral lesions since four months of age. 11 The reported mutation in this study is different from our presented case but was similarly in the RFXANK gene. As this mutation is considered serious and lethal and requires nonconservative treatments like HSCT.…”
Section: Discussioncontrasting
confidence: 83%
“…As this mutation is considered serious and lethal and requires nonconservative treatments like HSCT. 6 Given these new gene mutations, this suggestion is proposed that 11 should pay more attention to this gene in Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RFXAP protein consists of three regions, which are rich in acidic amino acids (DE), glutamine (Q), or basic amino acids (RK) reminiscent of a nuclear localization signal ( 12 ). Till date, only five different RFXAP gene mutations have been reported ( 2 ) with most of the mutations affecting the nuclear localization signal or DE regions. The RFXAP gene defect in exon 1 of our patients P1 and P2 also affects the nuclear localization signal and the mutation in intron 2 of patient P5 is expected to affect the formation of C-terminal domain, which is required for binding to the RFX complex ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…About two-third of these patients have a North African descent (Algeria, Morocco, and Tunisia) ( 1 ) and belong to complementation group B. A high prevalence of group A deficiency is reported in the European countries ( 2 ). A defect in the factors that regulate the expression of MHC class II genes resulting in the absence or reduced expression of MHC class II molecules on the immune cells is thought to be the underlying cause of MHC class II deficiency ( 3 ).…”
Section: Introductionmentioning
confidence: 99%